STRATEGI PEMGEMBANGAN BADAN USAHA MILIK DESA (BUMDes) DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT DESA - Firiadi (Jurnal Ilmiah Cano Ekonomos, 2023)
This article aims to find out the development strategy for Owned Enterprises Village (BUMDes) in improving the welfare of the community in Mahato Village North Tambusai District. This research was conducted using a qualitative approach descriptive method. Determining informants used purposive sampling technique. Informant Mahato Village Head, BPD Chair, community leaders, Mahato Village youth leaders, Agency Supervisor of BUMDesa Arwana Mahato, and manager of BUMDesa Arwana Mahato. Data obtained by observation, interviews and subsequent documentation studies Its validity was tested using source triangulation techniques. Data later analyzed by reducing data, presenting data and drawing conclusions. Results research shows that BUMDesa development strategies are improving Community welfare in Mahato Village includes the first organizational strategy, namely the formulation of the vision and mission involves stakeholders and the programs implemented are appropriate with the vision and mission of BUMDesa Arwana Mahato. Both resource support strategies It has not been implemented optimally because there are still obstacles. Third program strategy Judging from the BUMDesa Arwana Mahato program, it has had a positive impact on the BUMDesa and for the people of Mahato Village. So, there is no BUMDesa development strategy yet completely carried out optimally because there are obstacles in implementation BUMDesa development strategy.